Marketable Yield, Irrigation Production Efficiency and Economic return of Cabbage under variable Irrigation and Lateral Spacing - J.L.G. Kumar; Zafar, S.M.; Dubraj, A. (Journal of Soil and Water Conservation, 2022)
Field experiment was conducted at the Irrigation Research Farm of Allahabad Agricultural Institute-Deemed University, Allahabad, UP, during the rabi season of 2003-2004 (November to March) on clay loam soil to study the effect of four irrigation levels 50, 100, 150 and 200 per cent of pan evaporation replenishment and two lateral spacing 0.4 m and 0.8 m on yield, yield components, irrigation production efficiency and economic return of cabbage. The irrigation at 150 per cent of pan evaporation replenishment resulted the higher marketable head yield but irrigation production efficiency was higher with irrigation at 50 per cent of pan evaporation replenishment and decreased with increase in irrigation levels. The marketable yield, marketable head weight and irrigation production efficiency were higher when laterals were placed at every rows i.e., 0.4 m lateral spacing. The gross return, net return and benefit cost ratio increased with an increase in pan evaporation replenishment upto 150 per cent. A further increase in irrigation levels resulting form 200 per cent of pan evaporation replenishment decreased the gross return, net return and benefit cost ratio. The lateral spacing of 0.4 m and 0.8 m gave approximately same highest net return with irrigation at 150 per cent of pan evaporation replenishment. The seasonal water applied irrigation levels and marketable yield, gross return, net return and benefit cost ratio exhibits a strong quadratic relationship which can be used for optimizing the economic return under variable irrigation and lateral spacing.